First report of the gall midge Asphondylia serpylli on thyme (Thymus vulgaris), and identification of the associated fungal symbiont. (31st March 2017) - Zimowska, B.; Viggiani, G.; Nicoletti, R.; Furmańczyk, A.; Becchimanzi, A.; Kot, I.
Abstract: Asphondylia spp. (Diptera: Cecidomyiidae) are known for inducing gall formation on many diverse plants in both wild and agricultural contexts. The species Asphondylia serpylli is herewith reported for the first time on thyme ( Thymus vulgaris ) cropped in Poland. The associated fungus has been identified as Botryosphaeria dothidea, representing its first record from cecidomyiid galls on a species of Lamiaceae. Moreover, a short account is given on the parasitoid species active in this particular ecological context. These findings point out the basic role of B. dothidea in the organization of these three‐component biotic systems regardless of the varied assortments between the midge species and their host plant.